التصوير الفني في القرآن الكريم عند سيد قطب: مفهومه وخصائصه البارزة - Muhammad Naim Madjid (Jurnal Adabiyah: Humanities and Islamic Studies, 2018)
ملخص البحث يتحدث هذا البحث عن قاعدة التصوير الفني في القرآن الكريم حيث قام رائدها الشهيد سيد قطب بتطبيقها الواضحة في تفسيره الأدبي "في ظلال القرآن". ونقطة الانطلاق لهذا البحث تضع على المشكلة التي يعانيها معظم المسلمين اليوم في فهم الآيات القرآنية، خاصة في تعبيراتها المجازية. فلذلك، يعتبر الباحث بجديّة أن هذا البحث ضروري ومناسب لحل المشكلة وقضية التأويلات المنحرفة عن الصحّة والدقّة. ويهدف هذا البحث إلى إبراز المنهج الدقيق الموحي الذي سيرشد القارئين إلى فهم تعريف التصوير الفني مفصّلًا، وخصائصه البارزة الفائقة مع الأمثلة من الآيات القرآنية. وفي هذا البحث، قد استخدم الباحث المنهج التحليلي الوصفي للوصول إلى معلومات جلية ناصعة ونتائج موثوقة بها. وأهم النتائج التي توصّل إليها البحث إن التصوير الفني قاعدة مفضلة وطريقة دقيقة مؤثرة للتفاعل مع الآيات القرآنية المعجزة بصفة عامة، وتعبيراتها المجازية العميقة بصفة خاصة، وكان سيد قطب قد صوّر لونًا فنّيًا جديدًا في الدراسة القرآنية والأدبية.  الكلمات المفتاحية: التصوير، الفن، الخصائص البارزة، التعبيرات المجازية. (ARTISTIC IMAGERY IN THE HOLY QURAN BY SAYYID QUTUB: THE CONCEPT AND THE EMINENT CHARACTERISTICS) ABSTRACT This research talks about the theory of Artistic Imagery (AI) in the Holy Quran, where the martyr Sayyid Qutub as its pioneer developed and showed it into his literary exegesis “In the Shadow of Quran”. This research is based on the Muslim’s problem today in understanding of Quranic verses, especially in interpreting the metaphorical expressions. Therefore, the researcher considers seriously that this study is necessary and suitable for the salvation of the problem and arbitrary interpretation issue. This research aims to disclose the accurate and inspirational method which it conducts the readers to understand the detailed meaning of AI, and its eminent characteristics with the example of Quranic verses. The researcher uses the descriptive analytical approach in this research to arrive to the clear information and reliable results. Some important conclusions note that the AI is a preferred principle and exact approach and impressive to interact with the miracle of the Quranic verses generally and with the deep metaphorical expressions particularly, and it indicates that Sayyid Qutub has gave a new artistic color of Quranic studies and literary. Keywords: Imagery; Artistic; the Eminent Characteristics, the Metaphorical Expressions.